MONOPOLY PROHIBITION ACCORDING TO ISLAMIC LAW: A LAW AND ECONOMICS APPROACH - Arvie Johan (Fakultas Hukum Universitas Gadjah Mada, 2015)
Islamic law prohibits monopoly. The issue had arose since the advent of Islam, whereby it’s used as a strategy to maximize profit, has experienced rapid developments. This article assess the extent of Islamic law in prohibiting monopoly using law and economics approach. The result is that the exercise of caution shall apply in prohibiting monopoly. There are three steps needed in exercising the rule of caution: (1) defining monopoly as the absence of competition and lack of pricing options; (2) providing criteria of what causes monopoly in form of agreements between business competitors who can go against allocative efficiency effectively; and (3) direct the prohibition on monopoly towards agreement on explicit horizontal mergers and very large horizontal mergers which disregards quick mergers. Hukum Islam melarang monopoli. Isunya adalah sejak kedatangan Islam strategi pelaku usaha untuk memaksimalkan keuntungan telah berkembang pesat. Tulisan ini menentukan jangkauan hukum Islam untuk melarang monopoli dengan pendekatan hukum dan ekonomi. Hasilnya kehati-hatian dalam melarang monopoli. Tulisan menguraikan tiga langkah yang dibutuhkan: (1) memaknai monopoli sebagai ketidakhadiran persaingan dan ketiadaan pilihan harga; (2) memberikan kriteria monopoli berupa kesepakatan antar pelaku usaha pesaing yang mampu melawan efisiensi alokasi secara efektif; dan (3) mengarahkan larangan monopoli pada perjanjian horisontal eksplisit dan penggabungan berukuran besar.